Odpowiedzi

2010-01-25T23:19:00+01:00
R1 = 2Ω
R2 = 4Ω
R3 = 12Ω
U = 8V

Rz1 = R1 + R2
Rz1 = 2Ω + 4Ω = 6Ω

Rz = 1/Rz1 + 1/R3
1/Rz = 1/6Ω + 1/12Ω = 2/12Ω + 1/12Ω = 3/12Ω
Rz = 12/3Ω = 4Ω

I = U/Rz
I = 8V/ 4Ω
I = 2A

U12 = I * Rz1
U12 = 2A * 6Ω
U12 = 12V

I1 = U12/R1
I1 = 12V/2Ω
I1 = 6A

I2 = U12/R2
I2 = 12V/4Ω
I2 = 3A

U1 = I1 * R1
U1 = 6A * 2Ω
U1 = 12V

U2 = I2 * R2
U2 = 3A * 4Ω
U2 = 12V
Jak narazie wszystko sie zgadza :)

U3 = I * R3
U3 = 2A * 12V
U3 = 24V

I3 = U3/R3
I3 = 24V/12V
I3 = 2A

P1 = I(kwadrat) * R
P1 = I(kwad) * R1
P1 = 2A(kwad) * 2
P1 = 8W

P = 2A(kwadr) * 4Ω
P = 16W